Pengaruh Gaya Kepemimpinan Terhadap Kinerja Karyawan Divisi Collection PT. Adira Finance Cabang Pekanbaru - Husni Fuaddi; Deswita Deswita; Jacky Limayu (Sharing: Journal of Islamic Economics Management and Business, 2026)
This study aims to analyze the influence of leadership style on the performance of Collection Division employees at PT. Adira Finance Pekanbaru Branch. Leadership style plays an important role in shaping work behavior, motivation, discipline, and employee commitment that impact organizational performance. The study used a quantitative approach with a survey method by distributing questionnaires to all Collection Division employees. The sampling technique used was saturated sampling, so that the entire population was used as a research sample. Data were analyzed using descriptive statistics and simple linear regression to test the influence of leadership style on employee performance. The results showed that leadership style had a positive and significant effect on employee performance. The coefficient of determination (R²) value of 0.611 indicated that leadership style was able to explain 61.1% of the variation in employee performance, while the remaining 38.9% was influenced by other factors outside the study.